MODEL SUSCEPTIBLE VACCINATED INFECTED TREATMENT RECOVERED DENGAN KASUS KAMBUH DAN PENERAPANNYA (KASUS TUBERKULOSIS DI INDONESIA) - Lestari, Arifah Mufidah; Widyaningsih, Purnami; Sutanto, Sutanto (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2021)
Tuberculosis (TB) is caused by Mycobacterium tuberculosis. BCG vaccination is prevention the spread of TB in Indonesia. Individuals who are vaccinated (vaccinated) are healthy individuals and susceptible to infection. If a person is infected with TB then curative efforts through DOTS treatment must be carried out in order to recover. In the case of TB, recovered individuals may relapse. The susceptible vaccinated infected treatment recovered ( ) model with relapse cases is able to represent the spread of TB. This study aims to build the model with relapse, apply it to TB in Indonesia using data from 2004-2019, and interpret the results of implementing the TB-free target in Indonesia in 2050. The model is nonlinear first-order differential equations. The graph of the pattern of TB spread shows that all groups of individuals are experiencing an uptrend and it is predicted that the TB-free target has not been achieved. However, if the coverage of BCG vaccination and DOTS treatment is increased, contacts with TB sufferers are reduced, and relapse cases are reduced, it is predicted that the TB-free target will be achieved.